Management and Business Research - Easterby-Smith, Mark (SAGE Publications, Ltd. (UK), 2021)
This bestselling textbook has been fully updated, and provides readers with a comprehensive overview of methods for conducting business and management research. Highly visual, and written in a clear and accessible way, the book includes helpful learning features throughout, including learning goals at the start of each chapter, a research in action feature, examples, a Research Plan Canvas template and more. The content has been brought up-to-date with the inclusion of big data, predictive analytics and a dedicated chapter on machine learning. Accompanying the book is a wealth of online resources to further enhance your learning experience, including: MCQs Video content Templates and data sets Glossary flashcards Additional case studies These can be accessed by students at study.sagepub.com/easterbysmith7e